Moja Matura język polski podstawowy 1.0. - Kula, Julita; Potasz, Daniel (1974- ).; Sadowski, Michał (informatyka) (Presspublica, 2011)
Program zawiera 10 lekcji, składających się z ponad 200 stron z ćwiczeniami.